‘Secrets’ that kill: Crisis, custodianship and responsibility in ritual male circumcision in the Eastern Cape Province, South Africa - Kepe, Thembela (Social science & medicine (1982), 2010)
This paper analyses a tension between traditional leaders and the post-apartheid government in South Africa, concerning the crisis in ritual male circumcision. Over the last two decades, following ritual male circumcision, thousands of youth have been admitted to hospitals, hundreds have undergone penile amputations and hundreds have died. Following the government's intervention through legislation and other health measures, traditional leaders allege that this is a violation of cultural rights enshrined in the Constitution. Drawing on newspaper and journal articles, books, policy documents, and legislation, as well as informal interviews with initiates and their parents and field observations in the Eastern Cape Province (2002–2009), this paper explores the validity of the traditional leaders' challenge, arguing that the crisis in the ritual should be seen in a broader context than the tension between traditional leaders and the state. Finally, the paper argues the tension between traditional leaders and government, and the sensational reporting of this by the media, unfortunately takes away focus from the health crisis in the ritual.